The design and evaluation of bionic porous bone scaffolds in fluid flow characteristics and mechanical properties. (October 2022) - Li, Xinpei; Wang, Yanen; Zhang, Bo; Yang, Haozhe; Mushtaq, Ray Tahir; Liu, Minyan; Bao, Chengwei; Shi, Yikai; Luo, Zhuojing; Zhang, Weihong
Highlights: Evaluation and prediction of the permeability and fluid shear effect would be highly useful for improving the scaffold design process. Both the porosity and pore size affect the permeability of porous structure. Computational fluid dynamics can be used to study fluid shear stress of mass transport in bone scaffolds. Abstract: Background and objective: At present, there is a lack of efficient modeling methods for bionic artificial bone scaffolds, and the tissue fluid/nutrient mass transport characteristics of bone scaffolds has not been evaluated sufficiently. This study aims to explore an effective and efficient modeling method for biomimetic porous bone scaffolds for biological three-dimensional printing based on the imitation of the histomorphological characteristics of human vertebral cancellous bone. The fluid mass transport and mechanical characteristics of the porous scaffolds were evaluated and compared with those of a human cancellous bone, and the relationship between the geometric parameters (e.g., the size, number, shape of pores and porosity) and the performence of biomimetic porous bone scaffolds are revealed. Methods: The bionic modeling design method proposed in this study considers the biological characteristics of vertebral cancellous tissue and performs imitation and design of vertebrae-like two-dimensional slices images.It then reconstructs the slices layer-by-layer to form porous scaffolds with a three-dimensional reconstruction method, similar to computed tomography image reconstruction. By controlling the design parameters, this method can easily realize the formation of plate-like (femoral cancellous bone-like) or rod-like (vertebral cancellous bone-like) porous scaffolds. The flow characterization of porous structures was performed using the computational fluid simulation method. Results: The flow characterization results showed that the permeability of the porous scaffolds and human bone was 10 −8 ∼10 −9 m 2, and when the porosity of the porous scaffolds was higher than 70%, the permeability was higher than that of human vertebrae with a porosity of 82%. The maximum shear stress of the designed porous scaffolds and human vertebra were less than 0.8 Mpa, which was conducive to cell adhesion, cell migration, and cell differentiation. The results of 3D printing and mechanical testing showed good printability and reflected the relationship between the mechanical properties and design parameters. Conclusions: The design method proposed in this study has many controllable parameters, which can be adjusted to generate diversified functional porous structures to meet specific needs, increase the potential of bone scaffold design, and leave room for meeting the new requirements for bone scaffold characteristics in the future.